Cell block sensitivity for immunohistochemical detection of cytokeratin 5, oestrogen and progesterone receptors in canine primary mammary carcinoma - Silveira, Tatiane L. [UNESP]; Campos, Luciana M. [UNESP]; Dufloth, Rozany M. [UNESP]; Miot, Helio A. [UNESP]; Fêo, Haline B. [UNESP]; Montoya, Luis M. [UNESP]; Rocha, Noeme S. [UNESP] (Sistema de Bibliotecas UACH, 2017)
Mammary carcinomas are relatively common ailments among female canines aged around 10 years old, presenting an important morbidity with an average survival of five years. The cytoinclusion technique is frequently employed in human medicine as the investigative method of choice as it quickly provides resources for the determination of the correct therapeutic response, however, the effectiveness of the technique in canines remains understudied in veterinary medicine. This study aims at evaluating the degree of correlation with immunohistochemical marking for cytokeratin 5 (CK5), oestrogen and progesterone receptors (ER and PR) between the cytoinclusion and the histopathology technique in mammary carcinomas. Twenty-five samples of mammary carcinoma, both for the cytoinclusion and histopathological techniques were submitted for histological processing; microscope slides were created for hematoxylin-eosin (HE) staining and the immunohistochemical technique (IHC) was assessed for the ER, PR and CK5 receptors. Through the HE staining, we reached a concordance rate of 100% between the cytoinclusion and the histopathological analysis in the diagnosis of carcinomas. The immunohistochemical assay presented sensitivity of 85.71%, 95.45% and 100% and Cohen's kappa of 0.78, 0.84 and 0.95 for ER, PR and CK5, respectively, as well as 100% specificity and P<0.01 for all three markers. Therefore, cytoinclusion represents an accessible, fast and low-cost method, offering high sensitivity for the cytomorphological and immunohistochemical diagnosis of mammary carcinoma in female canines.
Keywords: Cytoinclusion; Histopathological; Immunohistochemistry; Tumor